VITAMIN D RECEPTOR POLYMORPHISMS AND LUNG CANCER: BIOLOGICAL RATIONALE, EPIDEMIOLOGICAL SIGNALS, AND TRANSLATIONAL IMPLICATIONS – A NARRATIVE REVIEW - GOGINENI RAJYALAKSHMI; MUNIINATHAN NATARAJAN; GIRIJA MENON M; SURESH ARUMUGAM A; KUPPUSAMY BASKARAN (Asian Journal of Pharmaceutical and Clinical Research, 2025)
This narrative review integrates mechanistic biology with population evidence to appraise when and why vitamin-D receptor (VDR) polymorphisms associate with lung cancer risk and outcomes. Using a systematic approach to searching, screening, and extraction across major databases, we included human observational studies (case-control/cohort), pooled analyses, and lung-specific functional experiments, focusing on incidence/risk, stage, overall/progression-free survival, and effect modification by smoking and vitamin-D axis status. A coherent, context-dependent signal emerges: TaqI (rs731236) shows the most reproducible susceptibility association, stronger in Asian ancestry, smokers, and non-small-cell lung cancer, while BsmI (rs1544410) and, in some settings, ApaI (rs7975232) tend to be protective; FokI (rs2228570) contributes to risk in certain populations and carries a pathway-level survival signal. Lung-specific evidence that ligand-activated VDR represses histidine-rich calcium-binding protein (HRC), curbing proliferation, migration, and xenograft growth, provides a credible mechanistic bridge from genotype to phenotype. However, heterogeneity in genotyping platforms and quality control, incomplete Hardy–Weinberg reporting, small or imbalanced cohorts, variable adjustment (smoking intensity, histology, stage), and sparse contemporaneous 25(OH)D and environmental data limit causal inference and impede quantitative synthesis in survival analyses. Taken together, current data support cautious, genotype-aware research use of the vitamin-D axis rather than routine clinical testing. Priority next steps include adequately powered, multi-ancestry cohorts with harmonised genotyping and prespecified covariates, standardised rsID-anchored genetic models, integrated vitamin-D/environmental measures, pathway-wide analyses across VDR–CYP27B1–CYP24A1–CYP2R1–GC, and prospective validation of genotype-augmented risk scores and NSCLC prognostic tools to test true translational utility.